Lichens and lichenicolous fungi of the Regional Landscape Park «Tiligulskiy» (Odessa region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The data on 120 species of lichenized and 12 species of lichenicolous fungi of Regional Landscape Park «Tiligulskiy» (Odessa region) are given. 43 of them are new for the Regional Park and 10 are excluded from list of lichen biota of this territory. Stigmidium mycobilimbiae Cl. Roux, Triebel & Etayo and Toninia subfuscae (Arnold) Timdal are a new species for Ukraine. Opegrapha centrifuga A. Massal. and Stigmidium glebarum (Arnold) Hafellner are secondly reported for the territory of Ukraine.
Keywords: Stigmidium mycobilimbiae, Toninia subfuscae, limestone, steppe.